The Probiotic Role of Lactic Acid Bacteria (LAB) in Helicobacter Pylori Gastritis - Arif Sabta Aji; Ranne Balqis (Indonesian Journal of Medical Sciences and Public Health, 2020)
Gastrointestinal tract infections are still common in developing countries such as Indonesia. Gastritis as a gastric health problem has a risk factor for developing into a peptic ulcer or stomach cancer. This literature review aims to discuss the role of probiotics against the incidence of gastritis caused by Helicobacter pylori infection. This article based on a literature review of the role of lactic acid bacteria probiotics in the treatment of Helicobacter Pylori infection. It was found that the probiotic role of Lactobacillus and Bifidobacterium was non-pathogenic and they were often used as probiotic mediators for H. pylori eradication. Probiotics affect the gastrointestinal tract through immunologic and non-immunological responses. Utilization of probiotic intake as one of adjuvant therapy in the treatment of gastritis disease might help the effectiveness of antibiotic drugs. But, to be used as a single therapy still needs further research.